Mastering JavaScript object-oriented programming : unleash the true power of JavaScript by mastering object-oriented programming principles and patterns - Chiarelli, Andrea (Community experience distilled., 2016)
ECMAScript 6 introduces several new object-oriented features that drastically change the way developers structure their projects. Web developers now have some advanced OOP functionality at their disposal to build large-scale applications in JavaScript. With this book, we'll provide you with a comprehensive overview of OOP principles in JavaScript and how they can be implemented to build sophisticated web applications.